Comparative Evaluation of Apically Extruded Debris with Protaper Gold, Reciproc Blue and Hyflex CM Instruments. (Mustansiria Dental Journal, 2024)
Aim of study: The target of the present investigation was to compare the amount of apically extruded debris with three endodontic nickel -titanium instruments; ProTaper Gold, Reciproc Blue and Hyflex CM .Materials and Methods: 30 mandibular premolars were separated into three groups according to the instrumentation methods (n=10) for every system, Protaper Gold, Reciproc Blue and Hyflex CM. After change of each file 5ml of 2.5% NaOCl was used as an irrigating solution with a 30G side vented irrigating needle, the apically extruded debris was collected in pre weighed glass vials, the samples were takeout and incubated at 68Co for 5 days to remove the liquid. The tubes were measured again, and the contrast between the first and last weight was calculated to determine the weight of the debris. The data were statistically analysed using One-way ANOVA analyses followed by Post hoc Tukey   LSD test.Result: Data obtained were statistically analyzed using One Way ANOVA and Post hoc Tukey LSD tests. All groups showed apical debris extrusion, The  ProTaper Gold systems extruded  more debris in comparison with other groups(0.0421)g, also the Protaper Gold group and Hyflex CM system showed statistically significant difference (p